A Novel Wireless Sensor Network Localization Approach: Localization based on Plant Growth Simulation Algorithm - Tang, Chengpei; Liu, Ruiqi; Ni, Jiangqun (Elektronika ir Elektrotechnika, 2013)
This paper proposes a novel wireless sensor network (WSN) localization algorithm. Accurate localization is the key technology of WSN. From various aspects many scholars consider localization problem, which is more effective to regard WSN localization problem as an optimization problem. Plant growth simulation algorithm (PGSA) is a kind of new intelligent optimization algorithm, which is intelligent simulation of plant growth in nature way. In addition to the common characteristics of intelligent algorithms, PGSA could be good robustness and guarantee the global optimal solution, etc. In this paper, further enhances the algorithm by adding the plant root of adaptive backlight function to effectively improve the computing speed and localization precision. Comparing this algorithm with simulated annealing algorithm (SAA), simulation results show that this algorithm has a higher and more consistent localization precision and faster computing speed. DOI: http://dx.doi.org/10.5755/j01.eee.19.8.5326